Implementation of Nursing Care for Clients with Stadium IIA Cervic Cancer in Anxiety Disorders with Benson's Relaxation in The Pavilion of Faith Sudjudi Floor II Gatot Soebroto Army - Ita Ita; Devita Rahmadhanty (Akademi Keperawatan RSPAD Gatot Soebroto, 2023)
Cervical cancer is a malignant process that occurs in the cervix, so that the surrounding tissue cannot carry out its functions as it should. The high incidence of cervical cancer in Indonesia has made cervical cancer a major health problem and one of the highest causes of death. It is noted that the incidence of cervical cancer in Indonesia is 36,000 cases or 9.2% of the total cancer cases and ranks second after breast cancer. Cervical cancer is a disease that causes psychological disturbances in the form of anxiety. One therapy that can reduce anxiety is benson relaxation. The purpose of this writing study is to describe nursing care for cervical cancer patients in anxiety disorders with Benson relaxation. The method used is descriptive research in the form of a case study. The characteristics of the subjects of this study were patients who experienced postoperative anxiety about cervical cancer with the HARS scale rating, with a score of 39 with a severe level of anxiety decreasing to 19 with mild anxiety. The results of this study found that in cervical cancer patients. after applying the Benson Relaxation technique can reduce the anxiety experienced by patients. The conclusion from this case study is that Benson's Relaxation Therapy is effective for reducing anxiety, from a score of 39 with a severe level of anxiety there is a decrease to 19 with mild anxiety.